Performance appraisal of interventions on rapeseed-mustard promoted through front line demonstrations under rainfed farming (Journal of Oilseed Brassica, 2026)
Present investigation was carried out to assess the performance and overall impact of technological interventions promoted through Front Line Demonstrations (FLDs) on rapeseed mustard by Krishi Vigyan Kendra (KVK), SKUAST-J, Doda in rainfed areas of Doda District. In all, 149 farmers on whose fields FLDs were laid out on improved varieties of rapeseed mustard, recommended seed rate, application of recommended doses of fertilizer and plant protection measures from rabi 2010-11 to rabi 2013-14 constituted the sample for the present investigation. Extension Gap (ExtGp), Technology Gap (TecGp) and Technology Index (TecInx) were calculated to assess the performance and overall impact of demonstrated technological interventions on rapeseed mustard. Technology Gap (TecGp) in the range of 431-499 Kg ha-1 for rapeseed and 380-640 Kg ha-1 for mustard, Extension Gap (ExtGp) in the range of 194-254 Kg ha-1 for rapeseed and 107-215 Kg ha-1 for mustard; and Technology Index (TecInx) in the range of 35.92-42.50 per cent for rapeseed and 31.67- 53.33 per cent for mustard were found. The percent increase in the yield of rapeseed for the technological interventions demonstrated through FLDs has been found to be in the range of 39.11 to 66.90 %. Similarly, in case of mustard crop, the per cent increase in yield has been found to be 23.62 to 42.82 % over the farmers’ practice.